2010
DOI: 10.1177/1082013209353090
|View full text |Cite
|
Sign up to set email alerts
|

Thin Layer Modeling of Tom Yum Herbs in Vacuum Heat Pump Dryer

Abstract: Thin layer vacuum heat pump drying experiments were conducted to determine drying models for Tom Yum herbs (chili, lemon grass, kaffir lime leaf and galangal slice). The drying experiments were conducted in a vacuum heat pump dryer at a constant drying pressure of 0.2 bars and drying temperatures ranging from 50 °C to 65 °C. The experimental results were fitted to a number of well-known thin layer drying models and it was found, for the range of drying temperature tested, that the Midilli model is the best mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Drying characteristics of apple pomace (Sun et al, 2007), grape seeds (Roberts et al, 2008), cocoa (Hii et al, 2009), garlic (Fernando et al, 2008), leafy vegetables (Sobukola et al, 2007) and tom-yum herbs (Artnaseaw et al, 2010) have been reported. Hot air oven drying of carrot pomace was reported by Upadhyay et al (2008) without considering effect of air velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Drying characteristics of apple pomace (Sun et al, 2007), grape seeds (Roberts et al, 2008), cocoa (Hii et al, 2009), garlic (Fernando et al, 2008), leafy vegetables (Sobukola et al, 2007) and tom-yum herbs (Artnaseaw et al, 2010) have been reported. Hot air oven drying of carrot pomace was reported by Upadhyay et al (2008) without considering effect of air velocity.…”
Section: Introductionmentioning
confidence: 99%
“…It can be done either in lower (−20°C to 45°C) or higher (45°C to +110°C) temperatures (Figure 1). Solar, microwave, infrared, and radio frequency HP systems require higher temperatures while chemical, vacuum and cooling with dehumidified HP systems operate at relatively low temperatures (Artnaseaw, Theerakulpisut, & Benjapiyaporn, 2010; Goh et al, 2011; Yadav et al, 2016; Yohana et al, 2018). Cooling with dehumidifier HP can be assisted with solar power, coulomb force, single or dual stage heat pumps, and so on (Goh et al, 2011; Minea, 2015).…”
Section: Low‐temperature Heat Pump Drying Methodsmentioning
confidence: 99%